Factors affecting effectiveness of knowledge management: A case of Bosnia and Herzegovina trade enterprises. (23rd May 2018) - Biloslavo, Roberto; Kljajić‐Dervić, Mirela; Dervić, Šemsudin
Abstract : The paper presents a conceptual model of factors affecting knowledge management effectiveness and determines whether knowledge management exerts a positive impact on business performance in trade enterprises of Bosnia and Herzegovina. Research data have been collected through a survey. The research sample was composed of 317 Bosnian companies that employ from 10 to 600 employees. Collected data were analysed by use of factor analysis and structural equation modelling. This is the first research carried out to prove influence of some organisational factors on knowledge management effectiveness in developing country such as Bosnia and Herzegovina by use of structural equation modelling. The research results suggest that organisational culture mediates the impact of human capital, information technology, organisational structure, and leadership on knowledge management effectiveness and confirm the hypothesis that the latter influences financial and nonfinancial indicators of business performance. The findings carry theoretical implications for knowledge management literature as they extend the scope of research on knowledge management from examining a set of independent organizational factors to examining a system‐wide mechanism that connects organisational elements and knowledge management effectiveness. The results of this study also provide a practical reference for the business when the latter considers investment into knowledge management system development, thus increasing their chance for success especially within developing countries.